2016
DOI: 10.3390/ijms17111923
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Total Phenolic Compounds and Antioxidant Activities during Ripening of Grapes (Vitis vinifera L., cv. Tempranillo) Grown in Semiarid Region: Effects of Cluster Thinning and Water Deficit

Abstract: A study was made of how water status (rainfed vs. irrigated) and crop load (no cluster thinning vs. cluster thinning) can together affect the grapes of Vitis vinifera cv. Tempranillo vines growing in a semiarid zone of Extremadura (Spain). The grapes were monitored at different stages of ripening, measuring the peroxidase (POX) and superoxide dismutase (SOD) antioxidant activities and the phenolic content (flavonoids and phenylpropanoids), together with other parameters. The irrigation regime was adjusted to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 58 publications
2
13
0
Order By: Relevance
“…The use of gibberellic acid (GA 3 ) to increase fruit yield was reported to decrease total phenolic, flavonoid and antioxidant activity in ‘Muscat’ grape berry skin and flesh, although levels in leaf, stem and tendril tissue increased [ 31 ]. Iincreasing high yield levels by contrasting levels of winter pruning or cluster thinning were also reported to result in lower total phenolic, anthocyanin and/or antioxidant activity in table grapes, and wine [ 30 , 32 , 33 ]. Garrido et al [ 33 ] also reported that the increase in phenylpropanoids and flavonoids concentrations effect resulting from cluster thinning/lower yields was greater in non-irrigated than irrigated grapes [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of gibberellic acid (GA 3 ) to increase fruit yield was reported to decrease total phenolic, flavonoid and antioxidant activity in ‘Muscat’ grape berry skin and flesh, although levels in leaf, stem and tendril tissue increased [ 31 ]. Iincreasing high yield levels by contrasting levels of winter pruning or cluster thinning were also reported to result in lower total phenolic, anthocyanin and/or antioxidant activity in table grapes, and wine [ 30 , 32 , 33 ]. Garrido et al [ 33 ] also reported that the increase in phenylpropanoids and flavonoids concentrations effect resulting from cluster thinning/lower yields was greater in non-irrigated than irrigated grapes [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Iincreasing high yield levels by contrasting levels of winter pruning or cluster thinning were also reported to result in lower total phenolic, anthocyanin and/or antioxidant activity in table grapes, and wine [ 30 , 32 , 33 ]. Garrido et al [ 33 ] also reported that the increase in phenylpropanoids and flavonoids concentrations effect resulting from cluster thinning/lower yields was greater in non-irrigated than irrigated grapes [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many factors can influence the composition and contents of bioactive compounds in fruits, like genotype, growth environment (soil, water, sunlight, etc.) and maturity, among which genotype usually has the greatest impact [ 24 , 25 , 26 ]. Thus, we could hypothesize that grapes with diverse genotypes should have different composition and contents of bioactive compounds, so it is worthwhile to assess the antioxidant capacities while determining the phenolic and flavonoid contents of peels and seeds from different grape varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Cluster thinning influences the yield reduction, advances grape maturity, improves the phenolic content of the grape, and influences the volatile profile of wine. In addition, this technique tends to diminish acidity and increase soluble solids [ 27 , 28 , 29 , 30 , 31 ]. Therefore, despite the economic impact of thinning, this process is a very common activity in some warm-climate producer areas.…”
Section: Introductionmentioning
confidence: 99%